2018
DOI: 10.4081/itjm.2018.940
|View full text |Cite
|
Sign up to set email alerts
|

Could clustering of comorbidities be useful for better defining the internal medicine patients’ complexity?

Abstract: Internal medicine patients are mostly elderly with multiple comorbidities, usually chronic. The high prevalence of comorbidity and multimorbidity has a significant impact on both positive responses to treatment and the occurrence of adverse events. Clustering is the process of nosography grouping into meaningful associations with some index disease, so that the objects within a cluster have high similarity in comparison with one another. In the decision-making process it is imperative that, in addition to unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…The analysis of multimorbidity patterns constitutes an effective and appropriate tool to model and assess the complexity of patients in terms of the diversity and statistical co-occurrences of their health conditions [15]. The literature on multimorbidity patterns was reviewed in 2014 by Pradros-Torres et al and in 2019 by Busija et al, and several methods and population contexts were identified [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of multimorbidity patterns constitutes an effective and appropriate tool to model and assess the complexity of patients in terms of the diversity and statistical co-occurrences of their health conditions [15]. The literature on multimorbidity patterns was reviewed in 2014 by Pradros-Torres et al and in 2019 by Busija et al, and several methods and population contexts were identified [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Our study applied a novel method of analysing multimorbities by clustering the general population of ED patients. To the best of our knowledge; and based on the review of Padros-Torres et al [22], where most studies focus on complex patient and chronic diseases [21][22][23][24][25], this is the first time that analysis of multimorbidity patterns has been used to cluster healthcare visits in a temporal analysis, and in this specific population . With our novel method, we extend the usage of theses methods to a global population with a low multimorbidity context and with a comprehensive clustering that was able to classify the vast majority of ED visits (92.93%).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the analysis of multimorbidity patterns is an appropriate tool to model the complexity of patients in terms of the diversity and statistical co-occurrences of their health conditions [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, worth considering a larger number of principal components in the analysis to explain a larger part of the data variability. Almost all the studies which have examined specific comorbidities start from a specific disease rather than examining all the co-occurring clinical and medical conditions [27,28]. Nosology clusters groups of diseases, disorders, or syndromes with meaningful associations into a type of classification, so that diseases, for example, within a cluster, are very similar to one another, but are dissimilar to diseases in other clusters [29].…”
Section: Overviewmentioning
confidence: 99%
“…To thoroughly analyze the data and identify the MRPs leading to adverse health outcomes-such as rehospitalization, nonreturn home, and early death [40,41]-among older adult inpatients, a literature review was conducted [27].…”
Section: Two-step Clustering Frameworkmentioning
confidence: 99%